Simulation and performance of 4-QAM, 8-PSK and 1024-QAM by using Reed Solomon codes in WCDMA environment / Ukhti Zulfah Amin - Amin, Ukhti Zulfah (2009)
This project illustrates the simulation and performance of 4-QAM, 8-PSK and 1024-QAM in WCDMA environment through Additive White Gaussian Noise (AWGN) channel and Rayleigh fading effect. These models consist of transmitter, transmission channel and receiver. This simulation is dealing with three channels. Channel 1 is using 4-QAM meanwhile channel 2 is using 8-PSK and channel 3 is using 1024-QAM. Reed Solomon Codes is use to encode and decode the signal of this three channels before modulation process and after demodulation process. The main objective of this project is to identify and compare which channel perform better by analyzing the performance of this three channel in term of bit error rate (BER) and signal energy to noise power density ratio ( Eb /N0 ). During this project, all the simulation processes that presented the performances of both the QAM and PSK is done by using software that is known as MATLAB version 7.6.